The Filipiniana Collections in Madrid - Lauron, Mona Lisa Q. (Journal of Philippine local history and heritage, 2016)
Madrid and Seville are two sites of large repositories of archival materials and artifacts that can help fill in the gaps in our history and contribute to a better understanding of our colonial past. Various Filipiniana manuscripts in Madrid and other parts of Spain are now at our fingertips. With the advancement of technology and the efforts of the Spanish government to digitize voluminous numbers of documents, we can now easily access these materials. This paper will give a glimpse of the libraries and archives of Madrid and introduce the development of online sources like the Portal de Archivos Españoles (PARES) and how these can be used in historical research.